Pengaruh Stress Kerja terhadap Kinerja Karyawan: Studi Kasus pada PT Sumber Cipta Multiniaga Djarum Cabang Yogyakarta (Progress, 2024)
This research aims to determine the effect of work stress on employee performance at PT Sumber Cipta Multiniaga Yogyakarta. Data collection techniques in this research were obtained by observation, interviews, questionnaires, documentation and literature study. The data source uses a questionnaire. The population in this study were all employees of PT Sumber Cipta Multiniaga Yogyakarta, totaling 37 employees. The sampling technique in this research was 100% of the total population so that the sample was 37 people. The data analysis technique used is simple linear regression analysis, coefficient of determination and partial testing (t test). The result of the simple regression equation is Y = 1.460+0.898X, meaning the constant value is 1.460. This means that if the work stress variable is 0 (zero), then the level or magnitude of the employee performance variable is 1,460. A value of 0.898 means that if the value of the work stress variable increases by 1 unit and other variables are considered constant, employee performance will increase by 0.898. The results of the calculation of the coefficient of determination show that the R Square is 0.526. This means that the work stress variable contributes 52% to employee performance. The remaining 48% of employee performance is influenced by other variables such as leadership, motivation and work environment. The results of the t test show that tcount is greater than ttable (6,227 > 1.689) and the significant level is (0.000 < 0.05), so Ho is rejected and Ha is accepted, which means there is a positive and significant influence between work stress on employee performance at PT Sumber Cipta. Multicommerce. Based on the results of the research and analysis that has been carried out, the author provides suggestions, namely PT. Sumber Cipta Multiniaga Yogyakarta should pay attention to and maintain the psychological condition of its employees, because this can result in a decline in employee performance